EXPLORING MALAYSIAN FOOD PREFERENCE AMONG VISITORS IN FOOD FESTIVAL - Dayana A.S; Shahril Faizal, A. J.; Sabeetha, S.; Syed Abdul Bari, S. (Journal of Islamic, Social, Economics and Development, 2023)
This study is related to the preference of Malaysian food among visitors who come and dine in at the Malaysia Food Festival programme, which was conducted from 14 to 16 September 2019 in Bukit Bintang, Kuala Lumpur. This study attempts to determine the level of Malaysian food preferences and Malaysian food choices. This study covered a questionnaire related to socio-demographics, publicity and promotion, factors that influence the choice of Malaysian food that visitors preferred to purchase and satisfaction levels towards the events. The questionnaire was given after the respondent had finished eating while being helped by a trained enumerator. Total respondents were 469 and majorities of them from Malaysia. In addition, the discount coupon and live promotion were the best platform of publicity to promote the event compared to others. Presentation of food including authenticity, price and description of food were the most factors that influenced respondent to spend here. The level of preferences of Malaysian food in Bukit Bintang, Kuala Lumpur received a very good and lively response from visitors and visitors were satisfied with various aspects of food choices, activities, location, price, and food presentation. Apart from that, the food that is the choice of Malaysian visitors to be realised as Malaysian food was a popular food known as nasi lemak, roti canai and sate